2020
DOI: 10.1016/j.cmet.2020.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Stabilizes TAZ in Hepatocytes to Promote Experimental Non-alcoholic Steatohepatitis

Abstract: Highlights d Liver cholesterol and TAZ are elevated in human and mouse fibrotic NASH d Increased hepatocyte cholesterol upregulates TAZ in human and mouse hepatocytes d Cholesterol blocks TAZ proteasomal degradation via an adenylyl cyclase-RhoA pathway d Silencing the pathway in hepatocytes lowers TAZ and fibrosis in experimental NASH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
143
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(153 citation statements)
references
References 76 publications
(108 reference statements)
7
143
1
2
Order By: Relevance
“…Intracellular cholesterol directly regulates gene transcription by suppressing SREBP2 activity, or indirectly via activating LXRs and farnesoid X receptor (FXR) by cholesterol-derived metabolites (oxysterols and bile acids, respectively). Moreover, the transcriptional regulator tafazzin (TAZ) has been identified as another cholesterol-sensitive pathway implicated in NASH progression [ 117 ]. Excess intracellular cholesterol stabilizes TAZ, which in turn activates the expression of pro-fibrotic genes in hepatocytes.…”
Section: Dyslipidemia: Linking Hepatic Lipid Metabolism and The Heartmentioning
confidence: 99%
“…Intracellular cholesterol directly regulates gene transcription by suppressing SREBP2 activity, or indirectly via activating LXRs and farnesoid X receptor (FXR) by cholesterol-derived metabolites (oxysterols and bile acids, respectively). Moreover, the transcriptional regulator tafazzin (TAZ) has been identified as another cholesterol-sensitive pathway implicated in NASH progression [ 117 ]. Excess intracellular cholesterol stabilizes TAZ, which in turn activates the expression of pro-fibrotic genes in hepatocytes.…”
Section: Dyslipidemia: Linking Hepatic Lipid Metabolism and The Heartmentioning
confidence: 99%
“…In a cohort of T2DM patients, a MUFA-rich diet induced a reduction in liver fat content [77], potentially through an increase in hepatic beta-oxidation [78]. In preclinical studies, dietary cholesterol has been shown to promote NASH and fibrosis, and contribute to HCC progression [79,80]. In human studies, high cholesterol levels have been associated mostly with cirrhosis and liver cancer [81].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Of note, cholesterol is consistently elevated in human and mouse fibrotic NASH. Its mechanistic link to NASH development has been explored recently [ 59 ]. Cholesterol upregulates the transcriptional regulator TAZ (transcriptional co-activator with PDZ-binding motif) and promotes fibrotic NASH through an adenylyl cyclase-calcium (Ca 2+ )-RhoA pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol upregulates the transcriptional regulator TAZ (transcriptional co-activator with PDZ-binding motif) and promotes fibrotic NASH through an adenylyl cyclase-calcium (Ca 2+ )-RhoA pathway. The importance of this cholesterol–TAZ pathway remains to be demonstrated in human NASH [ 59 ].…”
Section: Introductionmentioning
confidence: 99%